“O noivo e a noiva dizem vem!”: imagética nupcial na descrição do relacionamento entre Cristo e sua noiva no Apocalipse de João - Castro, Diego Vinícius de (2019)
Marriage rituals are part of man's daily life. From the beginning of humanity, they are present on the day of humanity. He is often responsible for marking cycles, making peace agreements between tribes, and, in their most widespread use, making alliances between persons and deities. The study of nuptial rites, therefore, becomes a reading proposal that goes beyond common sense; culminating in the interpretation of literary narratives from symbolic elements of marriage rituals. In the wedding imagery there is a lot of strength and life. After all, from caves, with their cave paintings, through the walls of Inca, Mayan and Egyptian pyramids, or sailing through the Nordic seas, docking in eastern lands, it can be observed that all uses of some rite to establish alliances between people or gods. When we come across a narrative of the Wedding of the Lamb in Revelation 19: 7-9: “Let us rejoice, and rejoice, and show glory; they approach the marriage of the Lamb. Your wife is ready. He has been given to be clothed with the most pure and resplendent linen” (For linen is the good works of the saints.) He then says to me, "Write, Blessed are the guests for the marriage supper of the Lamb". He said to me, "These are authentic words of God". It is observed - by a literary bias - that beyond all the imagery of the text, is present one of the greatest metaphors of Christianity: the marriage / union of Christ / Groom with his Church / Bride. This allegory, however, is not unique to New Testament writers. It begins in Genesis and just as a scarlet line runs through the entire Old Testament; being the chosen people / Bride and YHWH / Groom, culminating in the Wedding of the Lamb. This saga of the bridegroom hero, however, leaps from the imaginary field and transcends the physical world. Through this link Gennep makes a more practical reading of the marriage rituals, analyzing them from the perspective of social and behavioral behaviors. Through which members of a community take on new roles from bridal ceremonies. Following this line, Campbell - in proposing the hero's journey - in which an ordinary person crosses numerous thresholds to become a true hero - argues that the archetypes projected on bridal imagery contribute to the formation of each individual's social identity. In this dissertation, therefore, the objective is to offer a proposal to read various biblical narratives from the imagery lens of nuptial rites, analyzing their use to explain the relationship between God and man(AU)